Innovating forest science education through problem-based learning: Insights from a public university in Brazil - Lucena, Luiza; Robeson, Audrey; Falcão, Cassiano José Lages Marinho [UNESP]; Paulina, Lorena; Santana, Ana Clara; Hakamada, Rodrigo (Elsevier, 2025)
The evolving market's demand for forest science professionals with dynamic skills and interdisciplinary knowledge calls for an urgent and renewed look at forest science education methods to produce professionals ready to tackle ‘real world’ challenges and climate change issues. Integrating problem-based learning (PBL) in forest science education offers a promising avenue to align the current demand for dynamic forest science professionals and teaching approaches in forest science programs. However, while PBL has been extensively studied in various educational settings, limited research studies document its application in forest sciences education, particularly in the context of Brazilian public universities. This study explores the perceived learning outcomes of a group of forest engineering students exposed to PBL and the challenges associated with implementing it in a public university in Brazil. We developed a survey to assess the perceived learning outcomes of 32 students exposed to the PBL methodology. The survey instrument comprised nine questions designed to measure students' self-assessment of learning outcomes. Overall, we found that students reported the development of skills in field experience, technical knowledge, teamwork, communication, interpersonal relationship, and more. The findings from this study highlight the potential of PBL in forest science education and provide insights into how this approach can better prepare students to become dynamic forest science professionals.
Keywords: Education; Forest science; Learning outcomes; Problem-based learning (PBL); Professional development; STEM